Shelters and Their Use by Fishes on Fringing Coral Reefs - Ménard, Alexandre; Turgeon, Katrine; Roche, Dominique G.; Binning, Sandra A.; Kramer, Donald L. (PLOS ONE, 2012)
Coral reef fish density and species richness are often higher at sites with more structural complexity. This association may be due to greater availability of shelters, but surprisingly little is known about the size and density of shelters and their use by coral reef fishes. We quantified shelter availability and use by fishes for the first time on a Caribbean coral reef by counting all holes and overhangs with a minimum entrance diameter ≥3 cm in 30 quadrats (25 m2) on two fringing reefs in Barbados. Shelter size was highly variable, ranging from 42 cm3 to over 4,000,000 cm3, with many more small than large shelters. On average, there were 3.8 shelters m−2, with a median volume of 1,200 cm3 and a total volume of 52,000 cm3m−2. The number of fish per occupied shelter ranged from 1 to 35 individual fishes belonging to 66 species, with a median of 1. The proportion of shelters occupied and the number of occupants increased strongly with shelter size. Shelter density and total volume increased with substrate complexity, and this relationship varied among reef zones. The density of shelter-using fish was much more strongly predicted by shelter density and median size than by substrate complexity and increased linearly with shelter density, indicating that shelter availability is a limiting resource for some coral reef fishes. The results demonstrate the importance of large shelters for fish density and support the hypothesis that structural complexity is associated with fish abundance, at least in part, due to its association with shelter availability. This information can help identify critical habitat for coral reef fishes, predict the effects of reductions in structural complexity of natural reefs and improve the design of artificial reefs.